Urban Climate and Adaptation Tools (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
There is pressing evidence of phenomena, linked to meteorology and climate, which are modifying their temporal occurrence and which have a very evident impact on the safety and health of populations residing in cities. The urban problem at the beginning of the second set of twenty years of the new century requires a complete rethinking of the way of aggregation of man who, today, represents a large part of the world population due to increasingly accelerated urbanization processes over time. The human being has become a citizen, and within the city limits, he tries to develop his life expectancy by seizing opportunities from this. This search for well-being, understood as a complete state of man, at once physiological and psychological and social, can be thwarted by an urban structure that is not functionally capable of providing answers. The climate problem exacerbates this problem by strongly stressing the contradictions of living. Science, technology, and politics are today able to give answers if applied wisely in a joint effort, in a unit of language. This book proposes several solutions that can be implemented today, ranging from a full understanding of phenomena to adaptation policies for solving problems. The most pressing invitation is addressed precisely to politics to make cities more resilient and safe.